The Effect of Variety Seeking, Dissatisfaction, and Service Quality Toward Brand Switching on Netflix Streaming Service - Felicia, Ivana; Widyastuti (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to investigate the factors influencing brand switching behavior among streaming service subscribers in Indonesia, specifically focusing on the impact of consumer variety-seeking, dissatisfaction, and service quality on the decline of Netflix subscriptions. Design/Methodology/Approach: Conducted as a quantitative research endeavor, this study employs multiple linear regression analysis through the utilization of SPSS software. The research sample comprises 220 former Netflix subscribers who have transitioned to other streaming services. By examining the relationships between consumer variety-seeking, dissatisfaction, service quality, and brand switching, the study seeks to provide a nuanced understanding of the dynamics influencing subscriber preferences in the competitive streaming landscape. Research Findings: The findings of this study reveal compelling insights into the key drivers behind brand switching among streaming service subscribers in Indonesia. Consumer variety-seeking behavior, dissatisfaction with Netflix services, and perceived service quality emerge as significant factors contributing to the observed decline in Netflix subscriptions. The study underscores the importance of these variables in shaping consumer decisions and preferences in the increasingly competitive streaming market. Theoretical Contribution/Originality: This research contributes to the existing literature by shedding light on the intricate interplay between consumer behavior and brand switching in the context of streaming services. The study's originality lies in its exploration of the unique factors, namely variety-seeking, dissatisfaction, and service quality, influencing the migration of subscribers from one platform to another. By uncovering these dynamics, the research provides valuable theoretical insights that can inform both academia and industry stakeholders, offering a deeper understanding of the challenges and opportunities within the evolving landscape of streaming services in Indonesia.